Characteristics and outcome of pediatric and adult differentiated thyroid cancer with distant metastases - Alzahrani, Ali S.; Alobaid, Lulu; Albasri, Eman; Hadadi, Afnan; Hakami, Abdulrhman; Abothenain, Fayha; Alturki, Deema; Ewain, Najla; Howaidi, Ali; Alhindi, Hindi; Alskait, Ghada; Aljufan, Yasser; et al. (Frontiers in Endocrinology, 2026)
IntroductionPrevious studies suggested differences in the histopathological and molecular characteristics and outcome between pediatric and adult differentiated thyroid cancer (DTC). In this study, we focused on the characteristics and outcome of distant metastases (DM) between pediatric and adult patients with DTC.ObjectivesTo compare DM between pediatric (pDTC) and adult DTC (aDTC).Patients and methodsWe studied 35 pDTC (≤ 18 years) and 79 aDTC with DM seen over 20 years. The median age was 16 and 55 years and the F:M ratio was 3.4:1 and 1.7:1, respectively. Total thyroidectomy was performed in 91.4% and 93.7% and lymph node dissection in 94.3% and 64.6% of pediatric and adult patients, respectively. Radioactive iodine (RAI) ablation/therapy was administered to all patients except one.ResultspDM mostly involved a single organ (34/35), predominantly the lungs (32/35), and rarely the bone (2/35) and brain (1/35). By contrast, aDM were frequently multi-organ (45/79) involving lungs (72 patients), bone (50), brain (9), liver (10), kidneys (3), adrenal glands (2), breast (1) and soft tissues (3). Additional therapies (e.g. surgery, RAI) were administered to 28 and 78 pediatric and adult patients, respectively. At the last follow-up, only 1 (2.9%) vs. 6 (7.6%) patients had progressive metastases and 1 (2.9%) vs. 46 (58.2%) patients died due to DTC in pediatric and adult groups, respectively (P<0.0001). Other patients either were in an indeterminate status or had stable non-progressive metastases.ConclusionspDM mostly involve single organs and have good outcome and rare mortality. aDM are frequently multi-organ, progressive and associated with high mortality of 58% over about 4.5 years.